Financial Analysis for Replacement of Construction Equipment in Saudi Arabia (Construction Economics and Building, 2012)
This study report results of a survey conducted in the EasternProvince of Saudi Arabia to explore the procedures and financialtechniques that large-size contractors utilise in replacingequipment. The results indicated that contractors set severalreplacement alternatives that they evaluate by using a set ofvarious qualitative and quantitative factors. The contractors’business objectives, employee safety and morale, and, contractors’image in the industry were found to be the most influentialqualitative factors affecting the decision of equipment replacement.Inflation, downtime, obsolescence, salvage value, and depreciationare among the top quantitative factors that contractors considerwhile making a decision to replace equipment. Because of theirsimplicity and practicality, the net present value, payback period,and the economic life are the most popular techniques that areutilised for analysing the financial issues of proposed replacementalternatives.